Penguatan Ekonomi Pertanian melalui Peningkatan Kapasitas dan Inovasi Pengelolaan Usaha Pertanian di Universiti Teknologi MARA (UiTM) - Mia Lasmi Wardiyah (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) aimed to strengthen the agricultural economy by improving participants’ capacity and innovation in agricultural business management at Universiti Teknologi MARA (UiTM). The program employed a participatory approach through observation, needs identification, material delivery, discussion, practical activities, and evaluation. The activities covered agricultural economics, business management, identification of economic opportunities, value-added product development, innovation utilization, and agricultural product marketing strategies. Participants were actively engaged in discussions and practical activities to connect the learning materials with actual conditions and opportunities for agricultural business development. The results showed improvements across all evaluated indicators. The average level of participants’ understanding increased from 50.0% before the program to 82.5% after the activities, representing an improvement of 32.5 percentage points. The highest increase was observed in understanding agricultural product marketing strategies, which improved by 40 percentage points, while understanding of value-added development and innovation utilization increased by 35 percentage points each. These findings indicate that a combination of training, discussion, and practical activities can strengthen participants’ understanding of agricultural economics and innovation. The program is expected to encourage more innovative, productive, adaptive, and sustainable agricultural business management.